Selection criteria for electrical double layer structure regulators enabling stable Zn metal anodes. Issue 4 (16th March 2023) - Huang, Cong; Zhao, Xin; Hao, Yisu; Yang, Yujie; Qian, Yang; Chang, Ge; Zhang, Yan; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract : Combined with experimental and theoretical studies, we revealed a critical criterion that gives priority to the SEI-forming capability of additives for developing effective EDL structure regulators. Abstract : Regulating the electrical double layer (EDL) structure via electrolyte additives is a promising strategy to improve the cycling stability of Zn anodes, but there are no general strategies that can be used to rationally design EDL regulators for upgrading the Zn protection performance. Herein, by screening 15 solvent additives as EDL regulators, we reveal that the solid electrolyte interphase (SEI) capability of EDL regulators, instead of other parameters like the donor number, adsorption energy, and dielectric constant, predominately controls the cycling stability of Zn anodes. Specifically, the SEI capability of EDL regulators endows the Zn surface with a uniform and dense SEI layer, which physically isolates Zn anodes from electrolytes and induces dendrite-free Zn deposition. As a model electrolyte, 2M ZnSO4 solution with 0.5 vol% sulfolane enables Zn anodes to deliver high Zn plating/stripping reversibility under harsh test conditions. The compatibility of this designed electrolyte with V2 O5 and MnO2 cathodes is also demonstrated at low N/P ratios of 5.5 and 3.2, respectively.